On the Distinctively Human – Two Perspectives on the Evolution of Language and Conscious Mind - Osmo Kivinen; Tero Piiroinen (WILEY-BLACKWELL, 2022)
In this paper, two alternative naturalistic standpoints on the relations between language, human consciousness and social life are contrasted. The first, dubbed intrinsic naturalism, is advocated among others by the realist philosopher John Searle; it starts with intrinsic intentionality and consciousness emerging from the brain, explains language as an outgrowth of consciousness and ends with institutional reality being created by language-use. That standpoint leans on what may be described as the standard interpretation of Darwinian evolution. The other type of naturalism, in contrast, making use of the concept of evolutionary niches, suggests that the search for the explanatory mechanisms of language and consciousness should begin with the human community (of social action), because that is the cultural niche for everything distinctively human to evolve, including language and human consciousness.